Pedagogi Islam dan Modernitas Digital: Pembentukan Moral dan Integrasi Teknologi Berorientasi Nilai dalam Pendidikan Agama Islam - Saidah, Zahrotus; Nabila, Nabila; Munjiat, Siti Maryam; Akbar, Meiza Fajar (Pascasarjana UIN ANTASARI Banjarmasin, 2025)
The rapid digitalization of education has transformed Islamic Religious Education (PAI) while simultaneously generating significant pedagogical and normative challenges, particularly in sustaining Islamic pedagogy and moral–spiritual formation within digital learning environments. When digital media integration is not guided by value-oriented pedagogy, PAI risks becoming technocratic and instrumental, undermining its core mission of cultivating akhlaq karimah, religious consciousness, and ethical agency among learners. This study aims to analyze and formulate a digital media integration model for PAI learning in Cirebon that is pedagogically transformative and normatively grounded in Islamic educational values. Using a mixed methods approach with a sequential explanatory design, quantitative data were collected through a survey of 30 PAI teachers in schools and madrasahs in the Cirebon region, followed by qualitative data from open-ended interviews. Data were analysed using descriptive statistics and the Miles and Huberman qualitative model, drawing on TPACK theory, the SAMR model, and an Islamic pedagogy framework emphasizing the integration of ‘ilm, iman, and ‘amal salih. The findings indicate that digital integration in PAI remains largely at substitution and augmentation levels, yet reflective, contextual, and collaborative digital practices significantly enhance student engagement and moral internalization. The study concludes that effective digital integration in PAI requires a value-conscious Islamic pedagogical framework supported by institutional policy and continuous professional development.